Fitness Assessments of Women with Polycystic Ovary Syndrome: A Prospective Process Feasibility Study - Pamela J. Wright; Cynthia F. Corbett; Robin M. Dawson; Michael D. Wirth; Bernardine M. Pinto (IMR Press, 2023)
Background: Fitness is a marker of physiological and mental health. The purpose of this pilot study was to assess the feasibility of processes to recruit women with polycystic ovary syndrome (PCOS) during the Covid pandemic and collect their health and fitness data. Additionally, the data was used to explore possible associations between anthropometrics, PCOS biomarkers, health-related quality-of-life (HRQoL), and depressive symptoms with that of fitness and self-reported physical activity levels among women with PCOS. Methods: A convenience sample of women with PCOS (n = 15) were recruited via flyers and the snowball method. Participants completed surveys, anthropometrics, a dual energy x-ray absorptiometry scan, blood work, and a fitness assessment. Data were statistically analyzed using Spearman correlations. Results: Feasibility measures of recruitment and retention rates were 83% and 100%, respectively. Fidelity measurement for process averaged 97%. Participants (age 25.9 (± 6.2), mostly White (80%), single (60%), and employed full-time (67%)) were categorized as obese (body mass index (BMI) 32.2 kg/m2 ± 8.3, percent bodyfat 41.1% ± 8.1) with ≤1 comorbidity. Most participants were not regularly physically active and had high free testosterone levels (7.6 pg/mL ± 4.3), elevated high-density lipoprotein (63.2 mg/dL ± 12.9), fair cardiovascular capacity, and below average muscular strength/endurance. The following statistically significant and strong associations were found: (1) VO2 max with percent bodyfat (-0.59; p = 0.02), sex hormone binding globulin (0.73; p = 0.00), HRQoL (0.72; p = 0.00), and depressive symptoms (-0.67; p = 0.00), (2) abdominal strength with BMI (-0.66; p = 0.01) and high density lipoprotein (HDL) (0.59; p = 0.02), (3) physical activity level with percent bodyfat (-0.72; p = 0.00), and (4) resistance training with low density lipoprotein (LDL) (-0.52; p = 0.05). Conclusions: Collecting health and fitness data from women with PCOS is a feasible research approach. Randomized controlled trials in which health and fitness data are collected from women with PCOS are needed to confirm possible associations between fitness and PCOS clinical features and is in the planning process.